Culture-Led Urban Development vs. Capital-Led Colonization of Urban Space: Savamala-End of Story? - Jocic, Nikola (Urban Science, 2020)
The city quarter of Savamala, as an integral part of Belgrade, has had a very turbulent development path during the last two centuries. This path included several ups and downs, and culminated in tension over the last decade. Savamala fell into silent oblivion in the 20th century, but succeeded in re-emerging into the focus of the public and interest groups, mainly due to the cultural milieu that developed in this area at the beginning of the 21st century. The cultural vibes of the city quarter attracted various urban actors, who created a new image of Savamala. Eventually, cultural functions started to fade; however, after several years and through vague political decisions, Savamala became the part of the largest construction site in Belgrade, the Belgrade Waterfront. This article highlights the development of Savamala in the 2010s-from a forgotten city quarter to a rising cultural quarter and finally to the 'future centre of the city'. This analysis shows the participation of different stakeholders at different stages of development (their influence, power levels, and the mechanisms they used), as well as the footprints that urban development left in the quarter.
CRIS-Team WoS Importer:2021-03-05

Erdkabel-Systemdesign mit Unterstützung von Geodaten - Bertermann, David; Wagner, Jan; Jocic, Nikola; Schwarz, Hans; Stegner, Johannes (bbr - Leitungsbau, Brunnenbau, Geothermie, 2020)
Für das sich derzeit noch im Bundesfachplanungsverfahren befindliche ErdkabelGesamtvorhaben „SuedLink“ war es notwendig, im Rahmen der Studie „Thermische Bodenclusterung“ bereits zu einem frühen Projektzeitpunkt einen ersten Überblick über bodenphysikalische und klimatische Parameter mit Bedeutung für die Auslegung der Erdkabel zu gewinnen. Im Fokus stand u. a. die Bestimmung der Wärmeleitfähigkeit in Abhängigkeit der Tiefe und Lagerungsdichte sowie des Wasserhaushalts der jeweiligen Bodenart. Für die sich über die gesamte Länge des Erdkabel-Gesamtvorhabens erstreckenden Untersuchungsräume wurden digitale Flächen- und Bohrdaten der Landesämter sowie bundesweite Klimadaten genutzt. Alle Daten wurden in eine Geodatenbank implementiert und mithilfe eines Geoinformationssystems (GIS) prozessiert, interpoliert und visualisiert. <br
Keywords: Erdkabel; SuedLink; Boden; GIS

Mapping of Very Shallow Geothermal Potentials in Rural Areas: a Case Study of Bavaria (Germany) - Bertermann, David; Jocic, Nikola; Rammler, Mario; Schwarz, Hans; Wagner, Jan (Alternative Energy Sources, Materials and Technologies (AESMT’21), 2021)
Shallow geothermal energy is a renewable source for heating and cooling systems and buildings, by which a significant part of the arising energy demand could be covered if it is in widespread use. Especially in rural areas (very) shallow geothermal systems are well applicable due to the availability of spacious unsealed areas. The aim of the study was the examination of geothermal potential maps for utilization of very shallow horizontal applications in the rural areas of Bavaria (Germany). These potential maps should bring a more facilitated access to this issue for heating engineers and planners and with that a more common use of shallow geothermal energy. To develop these potential maps, the relevant parameters were implemented as areal data in a geographical information system (GIS). As database serves a soil map of Bavaria (scale 1:5000) which includes crucial parameters such as soil texture. Additionally, climate data based on degree-day numbers for characteristic regions were implemented. Soil and climate data provided the basis to develop an algorithm for calculation of (very) shallow geothermal potentials. Results are presented in two categories – thermal conductivity on the one hand, and heat extraction on the other. Thermal conductivity is the general parameter which describes local geothermal potentials, dependent on soil texture, bulk density and water content, while heat extraction is given as a system-specific characteristic. This research focused on four different shallow geothermal systems – horizonal ground heat collectors, capillary tube mats, geothermal baskets, and trench collectors. These geothermal potentials were processed in a GIS project enabling the output as potential maps. For validation of the very shallow geothermal potential maps soil data from selected case study municipalities were consulted. Therefore, data from geotechnical surveys and sampled and analysed soils were used. As a result, these maps revealing the very shallow geothermal potential can serve as handy tool for heating engineers and planners for an appropriate design of these horizontal geothermal applications. Afterall, the compilation process is easy to transfer to other regions, just by using respective soil maps and climatic dat
Keywords: Very shallow geothermal potential (vSGP); thermal conductivity; heat extraction; geothermal potential maps; GIS; rural areas

Pan-European planning tool for sustainable energy systems – ThermoMap project - Bertermann, David; Jocic, Nikola; Müller, Johannes (Book of Abstracts / 8th International Urban Geographies of Post-communist States Conference, 2019)

Renewable energy potentials for the post-socialist urban environments of Ub (Serbia) – A shallow geothermal approach - Müller, Johannes; Jocic, Nikola; Pozar, Tea; Bertermann, David (Book of Abstracts / 8th International Urban Geographies of Post-communist States Conference, 2019)

Renewable energy sources in a post-socialist transitional environment: The influence of social geographic factors on potential utilization of very shallow geothermal energy within heating systems in small serbian town of Ub - Jocic, Nikola; Müller, Johannes; Požar, Tea; Bertermann, David (Applied Sciences, 2020)
Energetic stability is a precondition for a regular functioning of society and economy. Actual climate change raised the awareness of population and policy makers about the importance of exploited energy sources. Renewable energy sources are revealed as the solution which should satisfy both needs-a need for energetic stability, as well as a need for producing 'clean' and 'sustainable' energy, and therefore reduce humans' influence on the climate change. Very shallow geothermal energy offers wide range for utilization, among others for heating and cooling living spaces. This article shows potentials of low temperature heating system networks in a small Serbian town of Ub. In addition to technical possibilities, this article combines geographical and social, as well as political and economic circumstances in the town of Ub, which emerge as a result of a complex (post-socialist) transitional vortex.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Low temperature district heating; Post-socialist transitional environment; Renewable energy sources; Very shallow geothermal potential (vSGP)